Adaptações observadas nas empresas emissoras de ADR durante o processo de harmonização com os padrões internacionais de Contabilidade - Costa, Ronaldo Mauricio (2015)
Accepting the countries to harmonize international accounting standards with IFRS, it changed the way of calculating the results of corporations worldwide. The convergence process transcended the accounting technical limits and required the companies, changes and adaptations that somehow changed the structure of the business and often the business management. The objective of this study is to analyze the changes and adaptations that have occurred in ADR issuers in the IFRS implementation process, identifying the financial, cultural and behavioral technical impacts in these companies. The search strategy was conducted by a multiple case study which analyzed in depth, four large corporations that are part of the ADR issuance program on the New York Stock Exchange and which went through the process of alignment with the international accounting standards. To this end, interviews were used, document analysis and participant observation was found that the process of convergence to IFRS improved the quality in the calculation of the results of companies and facilitated the comparison of the results with competitors. Existing systems before harmonization were adapted to receive the new accounting model. It was noticed also better positioning the counter on the companies command structure and an improved understanding of the importance of accounting for other areas of the companies, being supported by the employees of behavior change at all levels of the companies with greater interaction the departments. However there were no significant changes in the culture of corporations with the accounting harmonization process. Finally, in future studies it is recommended that a new search will be made to update the data and perception of cultural changes that take longer to happen